2007
DOI: 10.1258/095646207779949655
|View full text |Cite
|
Sign up to set email alerts
|

Performance of rapid HIV testing using Determine® HIV-1/2 for the diagnosis of HIV infection during pregnancy in Tijuana, Baja California, Mexico

Abstract: The aim of this study was to evaluate the performance of the rapid antibody test Determine HIV-1/2, in pregnant women at Tijuana General Hospital. Pregnant women seeking prenatal care or admitted in labour had blood drawn for a rapid HIV test (Determine HIV-1/2), enzyme immunoassay (EIA) and Western blot. Between March and November 2003, 1068 women in labour and 1529 women in prenatal care were enrolled. The sensitivity, specificity, positive and negative predictive values were 100%, 99.8%, 77% and 100%, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…It is a lateral flow assay with a 15-minute turnaround time. The Determine HIV-1/2 rapid test used has demonstrated 100% sensitivity and 99.8% specificity in pregnancy [14]. A second rapid HIV test (the First Response HIV Card Test) was performed on antenatal patients who had a positive Determine test.…”
Section: Methodsmentioning
confidence: 99%
“…It is a lateral flow assay with a 15-minute turnaround time. The Determine HIV-1/2 rapid test used has demonstrated 100% sensitivity and 99.8% specificity in pregnancy [14]. A second rapid HIV test (the First Response HIV Card Test) was performed on antenatal patients who had a positive Determine test.…”
Section: Methodsmentioning
confidence: 99%
“…To date, numerous research studies conducted in developed (i.e., USA and Canada) and developing (i.e., Brazil, Mexico, Cameroon, Russia, Rwanda, Nigeria, Uganda, Zambia, Peru and India) settings have demonstrated successful implementation of a rapid HIV testing program in labor and delivery [19–28].…”
Section: Barriers To Seeking Testing and Counseling Services In Pregnanmentioning
confidence: 99%
“…[21] Rapid testing has been conducted in parks, shelters, syringe exchanges, community clinics, VCT programmes and antenatal clinics. [21-25] The performance of algorithms employing several different POCTs either in consecutive or parallel testing strategies has also been reported, with varying outcomes. One field evaluation suggested that different combinations of POCTs provided sensitivity and specificity similar to standard enzyme immunoassays and Western Blot.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Another study evaluating the performance of the Determine HIV-1/2 in pregnant women in Mexico reported high sensitivity and specificity, though a lower positive predictive value associated with the low prevalence of anti-HIV in this population. [25] Another study reported successful implementation of rapid HIV testing in several different types of community settings but only measured the positive predictive value for those receiving confirmatory tests after testing anti-HIV positive on the rapid HIV assay. [21] A study employing the Determine and Uni-Gold rapid HIV test assays in Uganda reported good sensitivity, though specificity was compromised because of the occurrence of weak reactions with the test band.…”
Section: Introductionmentioning
confidence: 99%